Clinical significance of right ventricular–pulmonary arterial coupling in patients with tricuspid regurgitation before closure of atrial septal defect - Lee, Seon Hwa; Shin, Yu Rim; Kim, Dae-Young; Seo, Jiwon; Cho, Iksung; Lee, Sak; Kim, Jung Sun; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Background: Functional tricuspid regurgitation (TR) usually decreases after atrial septal defect (ASD) closure; however, it may persist and cause heart failure that requires treatment. We aimed to investigate clinical and echocardiographic factors predicting persistent TR after ASD closure. Methods: Among 348 adults who underwent isolated ASD closure between January 2010 and September 2020, 91 (26.1%) patients with significant TR (at least moderate degree) before ASD closure were included. Persistent TR was defined as significant TR on echocardiography at 6 months to 1 year after ASD correction. We comprehensively analyzed echocardiogram before ASD closure, including speckle tracking imaging. Right ventricular (RV)-pulmonary arterial (PA) (RV-PA) coupling was assessed by the ratio of RV global longitudinal strain (RV GLS) and tricuspid annular S’ velocity to PA systolic pressure (PASP). Results: Persistent TR was observed in 22 (24.2%) patients. Patients with persistent TR were significantly older and with larger TR jet area and lower RV-PA coupling parameters than those without persistent TR. On multivariable regression, persistent TR was independently associated with age [odds ratio (OR) 1.07, 95% confidence interval (CI) 1.01–1.14, p=0.030) and |RV GLS|/PASP (OR 0.001, 95% CI 0.00–0.017, p=0.012). |RV GLS|/PASP revealed a good predictive value for persistent TR after ASD closure (cut off 0.46, the area under the curve 0.789, p<0.001). Conclusions: Persistent TR after ASD closure is not rare. Old age and RV-PA uncoupling are associated with persistent TR after ASD closure. In older patients with abnormal RV-PA coupling, careful evaluation and concomitant or subsequent TR intervention may be considered.